Benefit of cerebrospinal fluid spectrophotometry in the assessment of CT scan negative suspected subarachnoid haemorrhage: A diagnostic accuracy study. Issue 1 (January 2015) - Hann, Angus; Chu, Kevin; Greenslade, Jaimi; Williams, Julian; Brown, Anthony
Abstract This study aimed to determine if performing cerebrospinal fluid spectrophotometry in addition to visual inspection detects more ruptured cerebral aneurysms than performing cerebrospinal fluid visual inspection alone in patients with a normal head CT scan but suspected of suffering an aneurysmal subarachnoid haemorrhage (SAH). We performed a single-centre retrospective study of patients presenting to the emergency department of a tertiary hospital who underwent both head CT scan and lumbar puncture to exclude SAH. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of an approach utilising both spectrophotometry and visual inspection (combined approach) was compared to visual inspection alone. A total of 409 patients (mean age 37.8 years, 56.2% female) were recruited and six (1.5%) had a cerebral aneurysm on angiography. The sensitivity of visual inspection was 50% (95% confidence interval [CI]: 12.4–82.6%), specificity was 99% (95% CI: 97.5–99.7%), PPV was 42.9% (95% CI: 10.4–81.3%) and NPV was 99.2% (95% CI: 97.8–99.8%). The combined approach had a sensitivity of 100% (95% CI: 54.1–100%), specificity of 79.7% (95% CI: 75.4–83.5%), PPV of 6.8% (95% CI: 2.6–14.3%) and a NPV of 100% (95% CI: 98.8–100%). The sensitivity of the combined approach was not significantly different to that of visual inspection alone (p = 0.25). Visual inspection had a significantly higher specificity than the combined approach (p < 0.01). The combined approach detected more cases of aneurysmal SAH than visual inspection alone, however the difference in sensitivity was not statistically significant. Visual xanthochromia should prompt angiography because of a superior specificity and PPV. Due to its reduced sensitivity, caution should be applied when using only visual inspection of the supernatant.